The Influence of Accounting Information Systems, Internal Control Systems, Human Resource Competence, Work Experience, and Utilization of Information Technology on the Quality of Financial Reports of MSMEs in Jember Regency - Muhammad fakih Khoirul Bais; Muhammad Firdaus; Muhammad Rijalus Sholihin (Medikun Publisher, 2024)
This study aims to determine the effect of accounting information systems, internal control systems, human resource competencies, work experience and utilization of information technology on the quality of financial reports, the type of research used is quantitative research. The data used is primary data with data collection techniques through questionnaires. The population in this study were all MSME actors in Sukowono District, Jember. The data collection technique used was the purposive sampling method and obtained a sample of 64 respondents. The data analysis method used was data instrument testing, classical assumption testing, multiple linear regression, coefficient of determination (R2) and hypothesis testing. The results show that accounting information systems, work experience, human resource competencies do not have a partial effect on the quality of financial reports. While the internal control system and utilization of information technology have a partial effect on the quality of financial reports. Simultaneously, accounting information systems, internal control systems, human resource competencies, work experience, and utilization of information technology have an effect on the quality of financial reports